Reconciliation of Spatial and Functional Transformation - Lokananta and Rumah Atsiri Adaptive Reuse - Saika, Raisa Maranta; Maheswari, Kirana Zhafirah; Agustiananda, Putu Ayu Pramanasari; Sinaga, Bryan Putra Parsada (Universitas Muhammadiyah Surakarta, 2024)
Buildings are constructed for a variety of different purposes according to the human activities within them. However, with the changing times, the function of buildings can become out of line with current needs. As a result, some buildings are abandoned, becoming neglected, or even damaged. Adaptive reuse can be one of the strategies to 'revive' abandoned buildings. This strategy is an important process in maintaining historic buildings because it can maintain, repair, replace, change, add to dismantle building elements while still avoiding damage to parts that have important value. This process is influenced by several factors, including the cultural integrity and architectural integrity of the building. Therefore, the purpose of this research is to understand the concept of adaptive reuse, in terms of spatial and functional adjustments based on the cultural and architectural integrity of a building. In this research, two museums, namely Lokananta and Rumah Atsiri became case studies. The research method used is the qualitative comparative method, which is to collect data based on existing data and direct observation such as documentation, interviews, and questionnaires. The results of the data from these two buildings were then analyzed by comparing the buildings before and after adaptive reuse to determine the effect of cultural and architectural integrity on changes in space and building functions.